POLITICAL INTEREST IN THE RECRUITMENT MECHANISM OF THE KPK’S COMMISSIONERS - Effendy, Revela Regilia; Manar, Dzunuwanus Ghulam (Journal of Politic and Government Studies, 2024)
This research was raised with the title “Political Interest in the KPK Commissioner Recruitment Mechanism”. The background of this research raises the issue of controversy and political interests that are in the process of electing KPK leaders in the 2019-2023 period. Through document tracing and stakeholder analysis, this thesis discusses what kind of political interests are being done in weakening the KPK, including the recruitment process. The finding of this study is the discovery of political interest in the election process of KPK leaders for the 2019-2023 period. Briefly, this discovery is evidenced by the many controversies that have arisen to the public. Starting from the 26 points of controversy contained in the 2019 KPK Law, controversies in the election process (KPK’s Pansel against the background of high conflicts of interest, Commission III of the DPR was detected to have the same interest, the President questioned his seriousness in choosing the 2019 KPK’s Pansel , and the final requirements that are mandatory for KPK leadership candidates to approve the 2019 KPK Law), the controversy over the National Insight Test which dismissed dozens of KPK employees, and the controversy over the extension of the KPK Commissioner's term of office for the 2019-2023 period to five years by the Constitutional Court. Analysis of this thesis discusses that it turns out the interests of oligarchs. It can be concluded that political interest in the election process of the KPK leadership is one of the many root problems where the problem is aimed at weakening the law in Indonesia, including the KPK. In short, the political elite conduct business activities in the state with the meaning that they control the law, they eradicate the righteous parties, and they also destroy the state. In this case, it is necessary to strengthen political will so that these interests are not found again and the KPK can return to functioning properly.